ANN-driven unfolding of epithermal neutron spectra in variable-geometry beam-shaping assemblies; Radiation Physics and Chemistry; Vol. 232 - Bedenko S. V. Sergey Vladimirovich; Polozkov S. D. Sergey Dmitrievich; Vlaskin G. N. Gennadiy Nikolaevich; Ghal-Eh Nima; Rahmani F. Faezeh; Veretennikov D. G. Dmitry Gennadjevich; Bagherzadeh-Atashchi S. Somayyeh (2025, 2025)
Title screen